AN EMPIRICAL EXPLORATION OF THE INTERPRETATION AND INVESTIGATION OF EDUCATIONAL PRINCIPLES IN MODERN SOCIETY - Bekturdieva Shahida Satiboldiyevna (Western European Studies, 2025)
This study delves into the intricate relationship between educational principles and their interpretation and investigation within contemporary societal contexts. Utilizing a mixedmethods approach, encompassing quantitative surveys and qualitative thematic analysis of expert interviews, we examine the evolution of pedagogical understanding and research methodologies. Our findings reveal a dynamic interplay between theoretical frameworks, technological advancements, and socio-cultural shifts, significantly influencing how educational principles are perceived and applied. Notably, the study highlights the tension between traditional pedagogical approaches and the emergent demands of digital literacy and personalized learning. This research underscores the necessity for a continuous, reflexive dialogue between educational theory and practice to ensure the relevance and effectiveness of pedagogical principles in a rapidly changing world
Keywords: Educational Principles; Pedagogical Interpretation